Factors Influencing the Ideality Factor of Semiconductor p-n and p-i-n Junction Structures at Cryogenic Temperatures - Abdullayev, Jo`shqin; Sapaev, Ibrokhim B. (East European Journal of Physics, 2024)
This article elucidates the dependence of the ideality factor on both internal functional parameters and external factors in semiconductors at low temperatures. We have explored the influence of external factors such as temperature and external source voltage. Through numerical modeling and theoretical analysis, we thoroughly investigate the dependencies of semiconductor material internal functional parameters—including doping concentration, the bandgap of semiconductors, the lifetime of charge carriers, and geometric dimensions ranging from micrometers to nanometers— the ideality factor on p-n and p-i-n junction structures. Our analysis spans cryogenic temperatures from 50 K to 300 K, with intervals of 50 K. To conduct this study, we have focused on p-n and p-i-n junction structures fabricated from Si and GaAs. The selected model features geometric dimensions of a=10 μm, b=8 μm, and c=6 μm. The thickness of the i-layer ranged from 10 µm to 100 µm in 10- µm increments. Increasing the thickness of the i-layer results in a corresponding rise in the ideality factor.